Intravenous immunoglobulins promote skin allograft acceptance by triggering functional activation of CD4+Foxp3+ T cells. - Tha-In, T; Metselaar, H; Bushell, A; Kwekkeboom, J; Wood, K (2010)
BACKGROUND: Intravenous immunoglobulins (IVIg) therapy is effective as a treatment for T-cell-mediated immune diseases, but whether and how IVIg suppress allogeneic T-cell responses is largely unknown. METHODS: In vitro, human CD4(+), CD4(+)CD25(-), or CD4(+)CD25(+) T cells were stimulated with allogeneic antigen-presenting cells (APCs), and mouse CBA/Ca (H2(k)) CD4(+) or CD4(+)CD25(-) T cells were stimulated with C57BL/10 (H2(b)) splenocytes, in the presence or absence of IVIg. Proliferation, binding of IVIg, expression of activation markers, and ZAP70-phosphorylation were determined. In vivo, 1x10(5) CD4(+) or CD4(+)CD25(-) T cells of CBA/Ca mice were adoptively transferred into CBA/RAG1(-/-) mice, which were 1 day later transplanted with skin grafts of C57BL/10 mice. IVIg was administered intravenously and skin graft survival was determined. RESULTS: IVIg bound to the surface of human and mouse CD4(+)Foxp3(+) regulatory T cells (Tregs). IVIg binding resulted in functional activation of Tregs, as detected by increased expression of surface activation markers, enhanced ZAP70-phosphorylation, and increased capacity to suppress allogeneic T-cell proliferation. IVIg inhibited allogeneic T-cell proliferation in the presence of Tregs, but this effect was abrogated on selective depletion of CD25(+) cells from responder T cells. IVIg prevented T-cell-mediated rejection of fully mismatched skin grafts in CBA/RAG1(-/-) mice reconstituted with CD4(+) T cells, but this effect was lost on selective depletion of CD4(+)CD25(+) cells from transferred T cells, indicating that IVIg induced dominant allograft protection mediated by Tregs. CONCLUSIONS: Our data show that IVIg suppress allogeneic T-cell responses by direct activation of Tregs. IVIg treatment, which has been proven safe, may have therapeutic potential in tolerance-inducing strategies in transplant medicine.